1993
DOI: 10.1177/41.2.7678271
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric analysis of envelope glycoprotein gp120 distribution on HIV-1 virions.

Abstract: The surface of HIV-1, like that of other retroviruses, is studied with virally encoded glycoproteins which appear ultrastructurally as electron-dense spikes or knobs. The glycoprotein that forms the spike structure, gp120, is non-covalently bound to the transmembrane glycoprotein gp41. Mature HIV-1 virions do not have as many spikes as the genetically related retroviruses HIV-2 and SIV. gp120 is lost from HIV-1 during viral morphogenesis and after incubation of the virus with the soluble form of cellular recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…Further analysis of purified VLP/gp41dmt4 by EM (Fig. 2C) indicated that the morphology and the size of purified VLP/gp41dmt4 was similar to those of HIV-1 VLPs previously reported [61]. Some baculovirus particles were observed by EM in the VLP preparations.…”
Section: Constructs Expression and Production Of Vlp/gp41 Variantssupporting
confidence: 81%
“…Further analysis of purified VLP/gp41dmt4 by EM (Fig. 2C) indicated that the morphology and the size of purified VLP/gp41dmt4 was similar to those of HIV-1 VLPs previously reported [61]. Some baculovirus particles were observed by EM in the VLP preparations.…”
Section: Constructs Expression and Production Of Vlp/gp41 Variantssupporting
confidence: 81%
“…As one of the better-understood examples, the influenza A virus, which is similar in size to HIV-1, has about 200 to 300 envelope glycoprotein spikes per virion and requires an average of 70 immunoglobulin G molecules to be neutralized (1,17,25,69,70,79). Understanding the stoichiometric requirements for antibody neutralization of HIV-1 is complicated by the replication defectiveness of the vast majority (greater than 99%) of HIV-1 virions (6,30), by the small number of intact envelope glycoprotein trimers per virion (12,20,30,85), by spontaneous and ligand-induced dissociation (shedding) of gp120 from the envelope glycoprotein complexes (40,50,59), and by potential heterogeneity among HIV-1 envelope glycoprotein complexes (6,21,51). For example, each HIV-1 virion has 7 to 14 envelope glycoprotein spikes, and an unknown fraction of these on any given virion are functional (12,30).…”
mentioning
confidence: 99%
“…From viral preparations produced optimally in vitro, it is estimated that only 1 in 10 4 to approximately 10 7 virus particles is infectious (33,36,38). The production of defective particles may be attributable to numerous causes, many of which point to a paucity of functional Env on virus particles (9,22,23,33,39,52,67). Levels of plasma virus can serve as a clinical indicator for disease progression (32,43,44) and viral transmission (60), but the extent to which cell-free plasma virus mediates viral dissemination still is unclear (21).…”
mentioning
confidence: 99%